Impact of Knowledge Management on Organizational Performance in Nepalese Commercial Banks - Sah, Siddharth Prasad (Nepalese Journal of Management, 2025)
This study examines the impact of knowledge management on organizational performance in Nepalese commercial banks. Organizational performance is the dependent variable. Similarly, the selected independent variables are knowledge acquisition, knowledge sharing, knowledge storing, information technology, and organizational culture. The primary sources of data are used to assess the opinions of respondents regarding knowledge acquisition, knowledge sharing, knowledge storing, information technology, organizational culture and organizational performance. The study is based on the primary data of 133 respondents. To achieve the purpose of the study, structured questionnaire is prepared. The correlation and multiple regression models are estimated to test the significance and impact of knowledge management on organizational performance in Nepalese commercial banks. The study showed a positive impact of knowledge acquisition on organizational performance. It indicates that high standard knowledge-based system leads to increase the organizational performance. Similarly, the study showed a positive impact of knowledge sharing on organizational performance. It indicates that culture of knowledge exchanged among the employees leads to increase the organizational performance. Likewise, the study showed a positive impact of knowledge storing on organizational performance. It indicates that effective knowledge storing mechanism leads to increase the organizational performance. Further, the study showed a positive impact of information technology on organizational performance. It indicates that better the information technology, higher would be the organizational performance. Moreover, the study also showed a positive impact of organizational culture on organizational performance. It indicates that adaptive organization culture leads to increase the organization performance.